Genetic and molecular basis of abnormal BOLD signaling variability in patients with major depressive disorder after electroconvulsive therapy - Siyu Fan; Yulin Zhang; Rui Qian; Jie Hu; Hao Zheng; Wentao Dai; Yang Ji; Yue Wu; Xiaohui Xie; Si Xu; Gong-Jun Ji; Yanghua Tian; et al. (Translational Psychiatry)
Abstract Electroconvulsive therapy (ECT) is an effective and rapid neuromodulatory intervention for treatment-resistant major depressive disorders (MDD). However, the precise mechanisms underlying their efficacies remain unclear. Resting-state functional magnetic resonance imaging (fMRI) data were collected from 84 individuals with MDD and healthy controls before and after ECT, and coefficient of variation of the BOLD signal (CVBOLD) analysis was combined with region of interest (ROI) functional connectivity (FC) analysis. To assess the reliability of the antidepressant mechanism of ECT, we analyzed the changes in CVBOLD in a separate cohort consisting of 35 patients with MDD who underwent ECT. Moreover, transcriptomic and neurotransmitter receptor data were used to reveal the genetic and molecular bases of the changes in CVBOLD. Patients with MDD who underwent ECT demonstrated increased CVBOLD in the left angular cortex and left precuneus. Following ECT, an increase in FC between the left precuneus and right lingual lobes was associated with improvements in Hamilton Depression Rating Scale (HAMD) scores. validation analysis consistently demonstrated similar changes in CVBOLD in two independent cohorts of patients with MDD. Moreover, these changes in CVBOLD were closely associated with thyroid hormone synthesis, oxidative phosphorylation, endocytosis, and the insulin signaling pathway, and were significantly correlated with the receptor/transporter density of serotonin and dopamine. These findings suggest that ECT modulates abnormal functions in the left angular cortex and left precuneus, leading to widespread changes in functional connectivity and neuroplasticity, especially in the default mode network, and exerts an antidepressant effect.